Patient management with head and neck tumors - a nationwide data collection in oral and maxillofacial surgery - Pabst, Andreas; Zeller, Alexander-N.; Goetze, Elisabeth; Hölzle, Frank; Hoffmann, Jürgen; Raguse, Jan Dirk; Wermker, Kai (Clinical oral investigations, 2024)
This study analyzed oncologic patient management from initial tumor diagnosis to tumor follow-up in oral and maxillofacial surgery (OMFS) in Germany. Material and methods: A dynamic online questionnaire with a total of 44 questions was used to generate general and specific data regarding oncologic patient management with head and neck malignancies, supportive care, and (pre-) rehabilitation from initial tumor diagnosis to tumor follow-up and head and neck cancer center (HNCC) structures in OMFS in Germany. The questionnaire was sent to 81 OMFS departments affiliated with the German-Austrian-Swiss Working Group for Tumors of the Jaw and Facial Region (DÖSAK) and the German Association of Oral and Maxillofacial Surgery (DGMKG). Data analysis was conducted descriptively. - Results: Forty-eight OMFS departments participated (response rate 59.26%), of which 36/48 (75%) were certified HNCC. 28/34 (82.4%) reported subjective improvements in oncologic care, most often interdisciplinary collaboration (21/33, 63.64%) and clinic structure changes (21/34, 61.76%). Nearly all OMFS departments present patients in multidisciplinary tumor boards (45/46, 97.83%) and aim for osseous reconstruction post-tumor resection (43/44, 97.73%). Significant discrepancies regarding the frequency of masticatory-functional dental rehabilitation following osseous reconstruction were observed. Before oncologic therapy, patients are offered various supportive services, mostly psychotherapy and psycho-oncological support (24/26, 92.31%). Post-therapy, speech therapy (43/43, 100%), physiotherapy (40/43, 93.02%), lymphatic drainage, and follow-up rehabilitation (39/43, 90.7%, respectively) are most often offered. 17/43 (39.53%) have oncological nursing staff. 36/40 (90%) manage patients and side effects during adjuvant therapy, while 5/41 (12.2%) provide proprietary palliative care. 36/41 (87.8%) offer counseling to patients and families. - Conclusion: Oncologic patient care in OMFS is highly standardized and potentially attributable to many certified HNCCs in Germany. Certain treatment aspects are handled differently, possibly due to institution-specific reasons.